Evaluation of MMP-7 A-181G and MMP-2 C-735T polymorphisms in healthy population from western Iran - Rahimi, Z; Yari, K; Rahimi, Z (Cellular and Molecular Biology, 2016)
Matrix metalloproteinases (MMPs) are involved in multiple physiological and pathological processes. Variable frequency of the MMPs gene variants might affect the susceptibility to certain diseases. The aim of present study was to investigate the frequency of MMP-7 A-181G and MMP-2 C-735T variants in healthy population of Western Iran with Kurdish ethnic background. Individuals were medical students and staff members of the Medical School of Kermanshah University and blood donors that consisted of 221 females and 94 males. Control subjects were free of general and genetic diseases. Two hundred and eighty available samples including 192 females and 88 males were studied for MMP-2 C-735T polymorphism. Genomic DNA was extracted from peripheral blood leukocytes. The MMP-7 A-181G and MMP-2 C-735T polymorphisms were detected using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method. The prevalence of MMP-7 G allele was 40% in studied individuals. The overall frequency of MMP-2 -735T allele was 15%. There was a higher frequency of MMP-2 T allele in females (16.9%) compared to males (10.8%, p=0.059). There were 30 (13.6%) women and 8 men (8.5%) with concomitant presence of MMP-7 AG and MMP-2 CT genotypes. All nine (4.1%) individuals with combined presence of MMP-7 GG and MMP-2 CT genotypes were women. The present study reports the frequency of two MMPs gene polymorphisms in healthy population of Western Iran. Our findings might be useful in evaluating the risk of MMPs in certain diseases. Also, our study suggests genetic admixture and similarities between our population with some Asian and European populations.